THE INFLUENCE OF UNDERSTANDING FAMILY FIQH ON MUSLIM FAMILY HARMONY IN THE AL-MUDATSIR STUDY GROUP - Khoirul Ahsan; Muhammad Abu Riva'i; Ramadhan, Abdul Rahman (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2025)
The research objectives is to analyse the effect of understanding family fiqh on Muslim family harmony. Family harmony, as a cornerstone of societal well-being, has garnered significant attention across diverse cultural and religious contexts, with the Islamic perspective offering a comprehensive framework for understanding and achieving familial contentment and stability. This research uses a quantitative approach with data collection methods through questionnaires. Respondents in this research were the Al Mudatsir recitation group, Sumbersari District, Jember. The variables analysed included understanding of family fiqh as the independent variable and family harmony as the dependent variable. The data analysis technique used was simple regression to measure the effect of understanding family fiqh on family harmony using JASP software. The finding of this research indicate that the understanding of family fiqh has a significant effect on family harmony in the Al-Mudatsir Jember research group. The magnitude of the influence of the understanding of family fiqh has a significant effect on family harmony in the Al-Mudatsir Jember research group is 19.8%. The remaining 80.2% is influenced by other factors not discussed in this research.